The relationship between fragmented QRS and mortality in without reversible defects patients with scintigraphical myocardial infarction diagnosis: The relationship between fQRS and mortality - Salan, Ahmet; Aksu, Ekrem; Köroğlu, Sedat; Doğaner, Adem (Journal of Surgery and Medicine, 2022)
Background/Aim: Evidence of increased mortality in perfusion abnormalities on myocardial perfusion scintigraphy (MPS) can be found. However, electrocardiography (ECG) is a cheaper and more easily accessible examination than MPS. Fragmented QRS (fQRS) is also considered to be associated with mortality in some cardiological diseases. The present study aimed to analyze the relationship between fQRS based on electrocardiography (ECG) and mortality in patients without reversible defects whose fixed hypoperfusion/perfusion defects were diagnosed and associated with myocardial infarction (MI) based on myocardial perfusion scintigraphy (MPS). Methods: Non-ischemic patients (2289 patients) with MI diagnoses based on scintigraphy were selected based on retrospective scintigraphy reports. The presence of fQRS was investigated in 85 patients whose 12-lead electrocardiographs could be accessed from the hospital archive, and their deaths due to all causes were questioned from the death information system. The relationship between left ventricular ejection fraction (LVEF), fQRS, type of exercise, number of leukocytes, other parameters, and mortality rates was analyzed. Results: The numbers of living (n = 69) and deceased (n = 16) patients were obtained. They were divided into two groups: (1) surviving patients (n = 69, number of fQRS positive 42) and (2) deceased (n = 16, number of fQRS positive 11). No distributional differences were found between mortality rates and fQRS and demographic features between groups (P = 0.558). However, a statistically significant effect was observed between mortality rates and low LVEF levels, pharmacological stress, number of leukocytes, and a low HDL level. Conclusion: The present study suggests that it may be useful to define benign features of fQRS. LVEF levels may be a very important parameter in decision-making for pharmacological stress, and its role in prediction of mortality may be higher than that obtained by fQRS.